Teaching and learning in higher education - Cleaver, Elizabeth (Sage, 2014)
It also includes: An overview of research methodology including data collection, literature reviews, good ethical practice, and research dissemination; Case studies of actual research projects to support understanding of how to carry out educational enquiry in practice.